العلاقة بين قلق الرياضيات و تحصيلها والاتجاه نحوها (دراسة ميدانية في مدارس محافظة اللاذقية ) - الفوال محمد خير إبراهيم; حسن علي أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدفت هذه الدراسة إلى حل المشكلة الآتية: معرفة العلاقة بين التحصيل في الرياضيات لدى طلبة الصف الثامن , وقلقهم من الرياضيات , واتجاهاتهم نحوها . أجريت هذه الدراسة على عينة من طلاب الصف الثامن بلغ عددها (149)طالباً وطالبة توزعت إلى (76) طالباً و(73) طالبة .وبعد تطبيق أدوات الدراسة في المدارس , بينت النتائج أن التحصيل في الرياضيات ارتبط مع بقية المتغيرات , حيث وجد ارتباط سلبي بين تحصيل الطلاب في الرياضيات وقلق الرياضيات عند مستوى دلالة 0.05 . ووجد ارتباط إيجابي بين اتجاهات الطلاب نحو الرياضيات والتحصيل في الرياضيات عند مستوى دلالة 0.05 وأشارت نتائج تحليل الانحدار المتعدد المتدرج إلى أن قلق الرياضيات والاتجاهات نحوها أسهما في تفسير تباين درجات الطلبة في الرياضيات , وقد أسهم متغير الاتجاهات نحو الرياضيات بمقدار أكبر في تفسير تباين درجات التحصيل في الرياضيات . وقد اقترح البحث تكليف المرشدين النفسيين في المدارس بالتعاون مع مدرسي الرياضيات بوضع خطط مشتركة للتعامل مع الطلاب الذين يعانون من مشكلة قلق الرياضيات , كما اقترح البحث وضع برامج إثرائية , لتساعد الطلبة في الرياضيات، موجهة للطلاب الذين يعانون قلق الرياضيات. This study aimed to determine the relationship between achievement in Mathematics and Mathematics anxiety and approaches toward this subject. The sample consisted of 76 male and 73 female students in the eighth grade. The results showed that achievement in mathematics was associated with the variables. There was a negative association between achievement in Mathematics and Mathematics anxiety at the indication level (0.05), and there was a positive association between achievement in Mathematics and approaches to Mathematics at the indication level (0.05). The results’ analysis of the multiple and gradual decline that both Mathematics anxiety and approaches to Mathematics helped in explaining the differences among students’ answers in Mathematics, but the approaches to Mathematics variable was of more help in explaining the differences in students grades in Mathematics. The research recommended to assign psychological counselors in schools who collaborate with Mathematics teachers to develop joint plans to deal with students who suffer from Mathematics anxiety problems. It also recommended to design programs that help enrich students’ competence, programs that can be addressed to students who suffer from Mathematics anxiety.